Multilevel determinants of paternal and child physical activity: qualitative research using dyadic interviews among Mexican heritage fathers living near the Texas-Mexico border - Marilyn E. Wende; M. Renée Umstattd Meyer; Serena Enriquez; Christina N. Bridges Hamilton; Tyler Prochnow; Joseph R. Sharkey (BMC Public Health)
Abstract Purpose Families living near the Texas-Mexico border face disproportionate barriers to physical activity (PA), yet little research has explored how Mexican-heritage fathers perceive and overcome barriers to child PA. The purpose of this study was to examine and describe fathers’ perceptions of strategies to improve child PA through a social-ecological lens. Methods Fathers (n = 30) living near the Texas-Mexico border colonias completed Spanish-language, father-father dyadic interviews (n = 15) conducted by trained facilitators. Spanish-language audio recordings were transcribed verbatim and translated into English. A coding framework was created based on the social-ecological model. Inductive and deductive approaches directed thematic analysis. Coding consisted of two researchers who coded one interview for reliability purposes with intercoder agreement set at 80% agreement on 95% of codes. Results Fathers mentioned multilevel barriers to PA, and outlined strategies that demonstrated their resilience in promoting PA among their children. Participants discussed intrapersonal factors (e.g., physical health, weight status) as barriers to their child’s PA, but their experiences with their own health issues motivated fathers to promote healthy behaviors in their children. Interpersonal factors (e.g., parental duty, social support, culture) facilitated PA, and were a major way fathers overcame unsafe outdoor environments to facilitate PA. Community and family supportiveness and closeness were cultural norms that were crucial for facilitating outdoor PA. Many fathers reported working long hours and having low access to well-paying jobs as a major barrier to PA. Given that fathers often came home from work late, participants developed creative solutions to facilitate outdoor PA, like installing lights to play outside at night. Finally, participants reported finding meaning in PA for themselves and their children, including connection with family and friends, culturally relevant activities, personal identity, and health maintenance. Conclusions The results of this study suggest that the meaning participants attribute to being physically active, especially on the interpersonal level, contributes to reinforcing PA and promoting resilience for themselves and their children. These findings can inform the design of culturally grounded interventions that leverage fathers’ interpersonal strategies and resilience (e.g., family-centered activities, addressing neighborhood safety) to support PA among children in low-resource, Mexican-heritage communities.